CLASSIFICATION AND APPLICATION OF GNSS METHODS AND TOOLS IN THE STUDY OF NATURAL DISASTERS: CLASSIFICATION AND APPLICATION OF GNSS METHODS AND TOOLS IN THE STUDY OF NATURAL DISASTERS - Petrova, Vesela (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
Global Navigation Satellite System (GNSS) is an umbrella term that refers to any satellite navigation system with global coverage. GNSS devices and receivers use geolocation information obtained from satellites to determine the current location of an object.